Differences in the virulence of two strains of Foot-and-Mouth Disease Virus Serotype A with the same spatiotemporal distribution - García Núñez, María Soledad (2010)
During the 2000-2001 epidemic of Foot-and-Mouth Disease Virus (FMDV) in Argentina, two FMDV serotype A viruses were identified among others. Since different pathogenic properties between these virus strains were noticed in cattle, we evaluated several biological properties and features of FMDV A/Arg/00 and FMDV A/Arg/01 in order to compare these viruses in terms of virulence and pathogenicity. Our results indicate that FMDV A/Arg/00 grows less efficiently than FMDV A/Arg/01, exemplified by smaller sized plaques, retarded one-step growth curves and overall low viral yields. Also, FMDV A/Arg/00 displayed the lowest specific infectivity in suckling mice requiring 50-fold more infectious particles than FMDV A/Arg/01 to generate a LD50 in suckling mice. Finally, FMDV A/Arg/00 did not cause death in adult C57Bl/6 mice even at high doses (107-106 PFU) whereas FMDV A/Arg/01 resulted lethal in doses as low as 102 PFU. Overall, we were able to demonstrate that these virus strains differ from each other in terms of virulence and pathogenicity.